2019
DOI: 10.1007/s00103-019-03063-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding vaccine acceptance and demand—and ways to increase them

Abstract: Vaccination saves millions of lives, and the World Health Organization (WHO) European Region celebrated record high coverage in 2018. Still, national or sub-national coverage is insufficient to stop the spread of vaccine-preventable diseases. Health authorities are increasingly aware of the need to prioritize the “demand” side of vaccination. Achieving high and equitable vaccination uptake in all population groups is not a quick-fix; it requires long-term investment in multifaceted interventions, informed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
142
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 32 publications
4
142
0
3
Order By: Relevance
“…The questionnaire was designed using the WHO TIP approach, 5 , 6 building on the COM-B model, 12 identifying necessary conditions for behaviour change: capability (individual ability to enact the behaviour), physical and social opportunity (external physical or social environments that enable or inhibit the behaviour) and motivation (individual mechanisms that enact or inhibit behaviour) ( Supplementary figure S1 ). Using a behaviour change model can ensure a comprehensive and systematic approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was designed using the WHO TIP approach, 5 , 6 building on the COM-B model, 12 identifying necessary conditions for behaviour change: capability (individual ability to enact the behaviour), physical and social opportunity (external physical or social environments that enable or inhibit the behaviour) and motivation (individual mechanisms that enact or inhibit behaviour) ( Supplementary figure S1 ). Using a behaviour change model can ensure a comprehensive and systematic approach.…”
Section: Methodsmentioning
confidence: 99%
“…3 , 4 On this background, the World Health Organization (WHO) Regional Office for Europe supports its Member States in exploring determinants of vaccination to inform interventions to increase vaccination and has developed guidance for this with the Tailoring Immunization Programmes (TIP) approach. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 As of 17th October 2020, the virus has rapidly spread in the Kingdom, causing a total of 341,495 laboratory-confirmed cases with 5144 deaths. 7 A vaccine is considered to be the most awaiting intervention 2,4,7 and hundreds of global R&D institutions engaged in unprecedented speed to develop the vaccine [7][8][9][10][11] However, public perception towards COVID-19 vaccine uptake is not available. Numerous studies have shown several factors responsible for vaccine acceptancy when a new vaccine is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…8 Vaccine acceptance and demand are complex in nature and context-specific, varying across time, place, and perceived behavioral nature of the community. [9][10][11][12][13][14][15] A study in Ireland showed that health care workers avoided seasonal influenza vaccination due to their misconception, efficacy, and trust in the vaccine. 16 In China, demographics and public perceptions are the predictors of vaccination acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…9 Another study conducted in Europe regarding the reasons and solutions for vaccine refusal and hesitancy placed emphasis on the following causes: perception of a high individual risk, complications observed due to vaccine experiences, distrust of health professionals, and psychological factors. 10 Particularly in Germany and England, socioeconomic development and educational level were found to be important factors related to vaccine rates and vaccine refusal and hesitancy. Families who refused vaccination were mostly of a high income level, and their education level was higher than the national average.…”
Section: Introductionmentioning
confidence: 99%